Multifunctional theranostic glyconanoprobes for synergistic eradication of breast cancer - Yigit Erdem G.; Goncu B. S.; Atasoy S.; Yildiz Uysal A.; Dag S.; Dag A. (My University, 2024)
Theranostic agents hold great promise for personalized medicine by combining diagnostic and therapeutic functions. Herein, two novel multifunctional theranostic glyconanoprobes targeting breast cancer were engineered for synergistic dual chemo-gene therapy and triple chemo-gene-photothermal therapy. Upconversion nanoparticles (UCNPs) were prepared and coated with a Dox-loaded glycopeptide polymer (P-Dox) to form UCNP@P-Dox for improving stability. UCNP@MP-Dox equipped for triple therapy was prepared by combining UCNP@P-Dox with magnetic (Fe3O4, M) nanoparticles with photothermal properties. To regulate the expression of the anti-apoptotic Bcl-2 protein, both UCNP@P-Dox and UCNP@MP-Dox were loaded with anti-Bcl-2 siRNA. Impressive photothermal efficiency and good MRI contrast were demonstrated in preliminary evaluations. Moreover, the UCNP@P-Dox/siRNA nanoprobe for dual therapy was shown in preclinical studies to significantly increase anti-tumor efficacy. In vivo experiments in tumor-induced mice showed nanoprobe accumulation in tumors and enhanced antitumor efficacy with combinatorial therapy over Dox and siRNA alone. This study demonstrates the tumor-targeting capability of multifunctional theranostic glyconanoprobes, establishing chemo-gene synergy as a potent therapeutic strategy for breast cancer.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Malzeme Bilimi Biyomateryal; Malzeme Bilimi; Mühendislik Bilişim Ve Teknoloji (Eng); Materials Science Biomaterials; Materials Science; Engineering Computing & Technology (Eng); Biyomalzemeler; Malzeme Bilimi (çeşitli); Genel Malzeme Bilimi; Fizik Bilimleri; Biomaterials; Materials Science (miscellaneous); General Materials Science; Physical Sciences